2019
DOI: 10.1016/j.apenergy.2019.03.174
|View full text |Cite|
|
Sign up to set email alerts
|

Forecasting the Impact of Connected and Automated Vehicles on Energy Use: A Microeconomic Study of Induced Travel and Energy Rebound

Abstract: Connected and automated vehicles (CAVs) are expected to yield significant

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…If the distribution of the per-unit externality, E , is log normal, with probability density function (4) φ…”
Section: Proofmentioning
confidence: 99%
See 1 more Smart Citation
“…If the distribution of the per-unit externality, E , is log normal, with probability density function (4) φ…”
Section: Proofmentioning
confidence: 99%
“…First, in general Parry and Small (2005) implicitly assume vehicle externalities are uncorrelated with the sensitivity of each vehicle's demand for gasoline and gasoline prices, whereas we allow for, and find, such correlation. 4 Second, we account for the possibility that marginal damage of vehicle emissions may vary geographically. Third, Parry and Small (2005) do not estimate the DWL that remains from instituting a gasoline tax, as opposed to the first-best set of optimal emissions taxes, which is one of the main focuses of our paper.…”
mentioning
confidence: 99%
“…However, despite recent hype, the uptake of car-sharing services has remained very limitedonly 1% of the population in the UK (Birch and Bullock 2019). A similar proposal is related to the automation of the vehicle fleet, an innovation for which the energy and carbon impacts are highly uncertain (Wadud, MacKenzie, and Leiby 2016;Taiebat, Stolper, and Xu 2019), but could possibly result in even more car-dependent transport systems (Papa and Ferreira 2018).…”
Section: Discussion: Places To Intervene In a Systemmentioning
confidence: 99%
“…This means that if CAVs increase their capacity and more vehicles are attracted to the road, CAVs' overall impact on total energy consumption is likely be negative. Along these lines, a recent microeconomic study has shown that the additional travel demand induced by CAVs can generate a rebound effect able to increase the overall energy consumption in road transport by up to 30% [19]. Similar dynamics may arise from the introduction of new transport options for last-mile freight delivery services (such as drones and automated robots).…”
Section: Increased Energy Efficiency Of Road Vehiclesmentioning
confidence: 97%